Aggressive Multiple Central Giant Cell Granulomas of the Jaws - Farnoush Mohammadi; Hoorieh Bashizadehfakhar; Sara Aliasghari; Zahra Gholamhoseini (Case Reports in Dentistry)
Central giant cell granuloma (CGCG) is considered a benign intraosseous lesion with a varied range of clinical features in two subtypes, including aggressive and non-aggressive lesions. This study presents a 9-year-old boy with multiple bilateral CGCG in the mandible without any systemic disease or specific syndrome. Clinical, radiographic, and histopathological findings demonstrated the aggressive lesions. It is discussed how the differential diagnosis and treatment can be determined based on the patient’s age as well as the size and manner of the lesion.